Masters Programs in Space Science and Engineering in Northern Sweden - Barabash, Victoria; Ejemalm, Johnny; Kuhn, Thomas; Milz, Mathias; Molin, Sven; Johansson, Jonny; Westerberg, Lars-Göran (Luleå tekniska universitet, Rymdteknik, 2017)
342